2007
DOI: 10.1111/j.1600-0501.2007.01404.x
|View full text |Cite
|
Sign up to set email alerts
|

A novel characteristic of porous titanium oxide implants

Abstract: The anodic-oxidized TiUnite implant has inherent photocatalytic activity. UVA illumination increases the surface hydrophilicity of the implant. However, this increase in hydrophilicity does not improve bone apposition to the implant surface at 4 weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
41
0
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 18 publications
1
41
0
1
Order By: Relevance
“…Anodic oxidized Ti surfaces have been reported to present hydrophilicity [38,39]. It has also been reported that anodic oxidized Ti surfaces have high surface energy [40,41], which is essential for maintaining surface hydrophilicity [42]. This suggests that the enhanced adsorption of fibronectin and reduction of albumin may be a result of surface energy-related hydrophilicity as well as Mg incorporation.…”
Section: Discussionmentioning
confidence: 99%
“…Anodic oxidized Ti surfaces have been reported to present hydrophilicity [38,39]. It has also been reported that anodic oxidized Ti surfaces have high surface energy [40,41], which is essential for maintaining surface hydrophilicity [42]. This suggests that the enhanced adsorption of fibronectin and reduction of albumin may be a result of surface energy-related hydrophilicity as well as Mg incorporation.…”
Section: Discussionmentioning
confidence: 99%
“…Using this principle, Wang et al [60] were the first to report on the increased hydrophilicity of crystalline TiO 2 surfaces upon UV irradiation. Indeed, anatase irradiated with UV-A becomes superhydrophilic, as numerous studies have shown since then [52, 61, 62]. Re-hydrophobization is also a well-known phenomenon of photocatalytic TiO 2 once hydrophilized by UV-A irradiation.…”
Section: Experimental and Marketed Dental Implant Surfaces: Wettinmentioning
confidence: 99%
“…Moreover, this efficient and cost-effective process presents a potential benefit to any commercially available implant surface and has shown positive host-to-implant response when implants were plasma treated immediately prior to placement in the surgical sites [3]. While promising results have been achieved by the atmospheric treatment of endosseous implants prior to placement, it is also of interest to evaluate whether such surface modification is effective over longer periods of time, since the surface may be contaminated when the implant is reexposed to air [14, 28]. Stachowski et al has reported that there is a possibility to maintain the high surface energy state of the titanium implant for at least 30 days, depending on various factors such as storage conditions [29].…”
Section: Introductionmentioning
confidence: 99%